2015
DOI: 10.14742/ajet.1878
|View full text |Cite
|
Sign up to set email alerts
|

Video-based feedback on student assessment: scarily personal

Abstract: Assessment feedback is an important part of students' learning experiences; however, textbased feedback has limitations. This article proposes an alternative in the form of individualised video recordings of the lecturer discussing each assignment. This research reports on 126 undergraduate and postgraduate students' reactions to 5-minute videos recorded by their teachers. The findings confirm that the majority of students valued the video feedback over text-based forms. In particular, video-based feedback was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
156
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(178 citation statements)
references
References 28 publications
15
156
3
4
Order By: Relevance
“…I liked the way she gives feedback and I waited for other videos." This finding is consistent with Henderson and Phillips (2015)'s study in which participants reported initial anxiety about playing screencast videos. Likewise, Matsumura and Hann (2004) found that computer anxiety can hinder the use of e-feedback.…”
Section: Disadvantages Of Screencastingsupporting
confidence: 91%
See 2 more Smart Citations
“…I liked the way she gives feedback and I waited for other videos." This finding is consistent with Henderson and Phillips (2015)'s study in which participants reported initial anxiety about playing screencast videos. Likewise, Matsumura and Hann (2004) found that computer anxiety can hinder the use of e-feedback.…”
Section: Disadvantages Of Screencastingsupporting
confidence: 91%
“…The analysis of data from the third stand revealed that more direct and indirect feedback was given on essays when using traditional written feedback than in audio format. Henderson and Phillips (2015) explored the attitudes of 126 undergraduate and postgraduate students towards receiving video-based assessment feedback on their assignments. The findings of the questionnaire showed that the majority of students felt positively towards veedback over text-based forms.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important for creative disciplines such as design, where assessment focuses on multifaceted aspects of visual and physical artefacts that may lend themselves to subjective, and potentially ambiguous, feedback. Videos have been linked to Media Richness Theory (see Henderson & Phillips ; Borup et al . ) proposed by Daft & Lengel (), which suggests that complex issues are best conveyed through rich media to reduce ambiguity.…”
Section: Exploring Video Feedbackmentioning
confidence: 99%
“…Videos for instructional teaching and demonstrations have been used for many years (Fortman & Battino, 1990) and videos are starting to be used for assessment feedback (Parton, Crain-Dorough & Hancock, 2010, Henderson & Phillips, 2015. There is however minimal literature that describes the use of student produced videos as an alternate form of assessment.…”
Section: Introductionmentioning
confidence: 99%